Estudo do efeito imunomodulador de antidepressivos de diferentes classes e de inibidores das isoformas de óxido nítrico sintase no modelo de depressão induzido por lipopolissacarídeo - Tomaz, Viviane de Sousa (2019)
Major Depressive Disorder (MDD) is among the leading causes of disability in the world. Research on the pathophysiology of this mental disorder that enables the discovery of new targets for its treatment has been widely conducted. The hypothesis of proinflammatory cytokines in depression, resulting, for example, from the response to psychosocial stressors, is fundamental in mediating the pathophysiological characteristics of MDD. In addition, depressed patients have increased blood LPS as a consequence of intestinal dysbiosis. In this context, administration of bacterial lipopolysaccharide endotoxin (LPS) or proinflammatory cytokines may cause depressive symptoms in rodents and humans. In this context, the aim of this study was to determine the effect of antidepressants on LPS-induced neuroimmune changes (protocol 1), as well as the role of nitric oxide synthase (NOS) isoforms in the inflammatory model of depression induced by systemic administration of LPS (protocol 2). For this purpose, behaviors related to MDD, such as behavioral despair, anhedonia and motivation, 24 hours after endotoxin administration were evaluated for the development of depressive behaviors, besides the evaluation of MPO activity and levels of TNF-α, IFN- γ and IL-1β, IL-4 and IL-6 in the brain, prefrontal cortex (CPF), hippocampus (HC), striatum (CE) and hypothalamus (HT) areas. The results from protocol 1 showed that exposure to LPS caused an increase in proinflammatory cytokines such as IL-1β and IL-6, as well as increasing Th1, TNF-α and IFN-γ response cytokines. These changes were prevented by the administration of tranilcipromin (TCP), amitriptyline (AMI), escitalopram (ESC), and vortioxetine (VORT) antidepressants, with particular attention to VORT which showed the best results in behavioral testing and neuroimmune assessments. In protocol 2, we observed that the NOS blockers, L-NAME, 7-NI and 1400 W, respectively total NOS blockers, neuronal NOS (nNOS) and inducible NOS (iNOS), were able to prevent changes in the despair test. behavioral, but only 7-NI was effective in preventing anhedonia symptoms through the sucrose preference test, as well as showing anxiolytic effect by exploring the open field center. Blockers showed distinct effects in relation to brain neuroimmune alterations, especially 7-NI and 1400 W. In general, this work points to a distinct immunomodulatory effect between antidepressants of different classes, especially vortioxetine, which showed better results. together with tranylcypromin as well as for a central role of nNOS in mediating depressive behaviors and LPS-induced neuroinflammatory changes.